﻿Phenology and morphology of the invasive legume Lupinus polyphyllus along a latitudinal gradient in Europe - Kristin Ludewig; Yves P. Klinger; Tobias W. Donath; Lukas Bärmann; Carsten Eichberg; Jacob Gadegaad Thomsen; Eugen Görzen; Wiebke Hansen; Eliza M. Hasselquist; Thierry Helminger; Frida Kaiskog; Emma Karlsson; et al. (NeoBiota, 2022)
Plant phenology, i. e. the timing of life cycle events, is related to individual fitness and species distribution ranges. Temperature is one of the most important drivers of plant phenology together with day length. The adaptation of their phenology may be important for the success of invasive plant species. The present study aims at understanding how the performance and the phenology of the invasive legume Lupinus polyphyllus vary with latitude. We sampled data across a >2000 km latitudinal gradient from Central to Northern Europe. We quantified variation in phenology of flowering and fruiting of L. polyphyllus using >1600 digital photos of inflorescences from 220 individual plants observed weekly at 22 sites. The day of the year at which different phenological phases were reached, increased 1.3–1.8 days per degree latitude, whereas the growing degree days (gdd) required for these phenological phases decreased 5–16 gdd per degree latitude. However, this difference disappeared, when the day length of each day included in the calculation of gdd was considered. The day of the year of the earliest and the latest climatic zone to reach any of the three studied phenological phases differed by 23–30 days and temperature requirements to reach these stages differed between 62 and 236 gdd. Probably, the invasion of this species will further increase in the northern part of Europe over the next decades due to climate warming. For invasive species control, our results suggest that in countries with a large latitudinal extent, the mowing date should shift by ca. one week per 500 km at sites with similar elevations.